Fractionated γ-irradiation renders tumour cells more responsive to apoptotic signals through CD95 - Sheard, Michael; Krammer, Peter H.; Žaloudík, Jan (British journal of cancer, 1999)
Signals through the CD95 surface receptor can specifically induce apoptosis. Some tumour cell lines are sensitive to CD95 signals, and insensitive cells can be converted to a sensitive phenotype if given appropriate treatment. To determine whether the apoptotic response of tumour cells to signalling through CD95 might be enhanced by ionizing irradiation, carcinoma cells were treated with either single-dose or fractionated γ-irradiation. The response to treatment with an agonist anti-CD95 antibody was enhanced by pretreatment with either a single large dose or daily fractionated radiation. Fractionated irradiation induced cumulative and prolonged up-regulation of CD95 expression in cell lines bearing functional p53. Since two of four cell lines exhibiting heightened responsiveness to CD95-mediated signals following fractionated irradiation express mutant p53 and displayed little or no up-regulation of CD95, enhanced responsiveness did not correlate with p53 status and CD95 up-regulation. Continuous inhibition of CD95/CD95-ligand interactions during fractionated irradiation provided no protective effect to cells, arguing that autologous CD95/CD95-ligand interactions did not contribute to the direct lethal effect of irradiation. We conclude that fractionated γ-irradiation provides an extended period of time when carcinoma cells are more responsive to CD95-mediated signals in vitro.